Fragmentation Processes During Strombolian Explosions Revealed Using Particle Size Distribution Mapping - Colo’, Livia; Ripepe, Maurizio; Gurioli, Lucia; Harris, Andrew J. L. (Frontiers in Earth Science, 2020)
Fragmentation dynamics can be described by the size distribution of the fragments generated during an explosion. We approach the problem of magma fragmentation during a Strombolian explosion using the grain size distribution (GSD) of a ballistically emplaced lapilli-and-bomb deposit. We present a novel method of collecting juvenile fragments landing in a well-defined near-vent zone (around 50 m from the source). The method uses four plastic sheets (tarpaulins or tarps) deployed below the SW crater rim of Stromboli volcano (Aeolian Islands, Italy). Due to the vicinity of the collection site to the vent, the fragments were still hot when they landed and created a map of melt holes on the sheets. This map was processed to calculate cumulative fragment size distributions (FSD) and grain size distributions (GSD). The cumulative FSD (number based) and GSD (mass-based) are best described by unique power laws with fractal dimensions of 1.40 and 2.03, respectively, testifying to the fractal nature of fragmentation. The fractal dimension is consistent with low energy fragmentation of a brittle material. This method represents a new way of measuring fragmentation dynamics and classifying volcanic eruptions according to their fragmentation energy.